History of Metallurgy on the Territory of Sisak and Banovina - Lazić, Ladislav (Array, 2009)
The manufacturing of basic metals and metal products has a long tradition in Croatia, particularly, in Sisak. Since Halstatt period onwards today's Sisak has continually been settled. At the same time, Sisak has always, in all historic periods, been closely connected with the production of iron and iron products as its most important industrial branch. Metallurgy in the territory of today's Sisak and Banovina, as a region os Sisak-Moslavina County, was developed from Vučedol as well as Celtic and Roman culture. In this paper is given a historical overview of the development of metallurgy in this area with emphasis on the Celtic and Roman period, which gives significant importance to the Sisak, among others, as one of the most important metallurgical center in the territory of today's Europe.